2017
DOI: 10.3892/etm.2017.5218
|View full text |Cite
|
Sign up to set email alerts
|

Radix Cyathula officinalis Kuan inhibits arterial remodeling in spontaneously hypertensive rats

Abstract: There is still no resolution for arterial remodeling related with hypertension, though hypertension treatment has access to a number of pharmacological agents. The present study aimed at investigating the prevention of Cyathula officinalis Kuan's roots (C. officinalis Kuan) against in arterial remodeling in vitro. Spontaneously hypertensive rats (SHRs) were intragastrically administered 3, 6 or 12 g/kg C. officinalis Kuan or normal saline or enalapril (2.5 mg/kg) once a day for 8 weeks. Hematoxylin and eosin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Modern pharmacological studies showed that Achyranthes bidentata polysaccharides can promote cellular immunity and antitumor properties and reduce peripheral leukocyte reduction induced by cyclophosphamide [22]. CR also contains glycine, valine, citramalic acid, ribonic acid, pipecolinic acid, N -carbamylglutamate, gluconic acid, 3-hydroxypropionic, glutaric acid, cellobiose, lactic acid, gluconic acid, xylitol, glutaric acid, pipecolinic acid, ribonic acid, mannose, oxalic acid, digalacturonic acid, lactic acid, 2-deoxyerythritol, acetol, 3-hydroxybutyric acid, N -carbamylglutamate, cellobiose, and palmitic acid [23, 24].…”
Section: Phytochemistrymentioning
confidence: 99%
“…Modern pharmacological studies showed that Achyranthes bidentata polysaccharides can promote cellular immunity and antitumor properties and reduce peripheral leukocyte reduction induced by cyclophosphamide [22]. CR also contains glycine, valine, citramalic acid, ribonic acid, pipecolinic acid, N -carbamylglutamate, gluconic acid, 3-hydroxypropionic, glutaric acid, cellobiose, lactic acid, gluconic acid, xylitol, glutaric acid, pipecolinic acid, ribonic acid, mannose, oxalic acid, digalacturonic acid, lactic acid, 2-deoxyerythritol, acetol, 3-hydroxybutyric acid, N -carbamylglutamate, cellobiose, and palmitic acid [23, 24].…”
Section: Phytochemistrymentioning
confidence: 99%
“…JYYS granule has been a therapeutic drug for hypertension and early hypertension-caused renal damage by downregulating AngII and TNF- α level [32]. Extracts from Bidens pilosa, Cornus officinalis, Fallopia multiflora, Cyathula officinalis , and Alisma plantago-aquatica may ameliorate hypertension and renal injury [2426] and show antioxidant activity [27], inhibit arterial remodeling in spontaneously hypertensive rats [28], and exhibit significant anti-chronic-prostatitis and anti-inflammatory activities [2931]. In this study, the data also demonstrates that JYYS granule, in a dose dependent manner, could significantly decrease urinary albumin and β 2-MG excretion, and it ameliorates renal pathological changes and suppresses expression of profibrogenic genes and extracellular matrix genes including renal collagen-I, fibronectin, PAI-1, TGF β 1, TIMP-1, and collagen-IV.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from Fallopia multiflora show antioxidant activity [27]. Extracts from Cyathula officinalis inhibit arterial remodeling in spontaneously hypertensive rats [28]. Components from Alisma plantago-aquatica show significant anti-chronic-prostatitis activity, anti-inflammatory, and antioxidant activities [2931].…”
Section: Introductionmentioning
confidence: 99%